2023
DOI: 10.3390/su151813493
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning and Artificial Intelligence in Sustainability: A Review of SDGs, Renewable Energy, and Environmental Health

Zhencheng Fan,
Zheng Yan,
Shiping Wen

Abstract: Artificial intelligence (AI) and deep learning (DL) have shown tremendous potential in driving sustainability across various sectors. This paper reviews recent advancements in AI and DL and explores their applications in achieving sustainable development goals (SDGs), renewable energy, environmental health, and smart building energy management. AI has the potential to contribute to 134 of the 169 targets across all SDGs, but the rapid development of these technologies necessitates comprehensive regulatory over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…If seasonal patterns are needed in the time series, the seasonal term is added to ARIMA and becomes the seasonal ARIMA model (SARIMA). The model can be written as Equation ( 5) [63].…”
Section: Arima and Sarima Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…If seasonal patterns are needed in the time series, the seasonal term is added to ARIMA and becomes the seasonal ARIMA model (SARIMA). The model can be written as Equation ( 5) [63].…”
Section: Arima and Sarima Modelsmentioning
confidence: 99%
“…smoothing_level determines the smoothing coefficient of the error component, smoothing_trend determines the trend component's smoothing coefficient, and smoothing_seasonal determines the smoothing coefficient of the seasonal component. These coefficients affect how "close" or "smooth" the model will be to the data [62,63,[65][66][67].…”
Section: Ets Modelmentioning
confidence: 99%
“…In waste management, AI reduces fuel consumption and emissions, increases recycling rates, and reduces landfill waste ( 143 ). GeoAI is one of the emerging AI tools that can handle complex spatial and temporal data to adjust algorithms and workflows according to the specific characteristics of spatial processes ( 136 , 144 ). It can develop various environmental exposure models across different geographical regions in prospective and retrospective approaches ( 136 ).…”
Section: Ai In Environmental Healthmentioning
confidence: 99%
“…DL algorithms are ANNs with a deep architecture that are capable of processing enormous amounts of data; they have outperformed state-of-the-art results in a variety of classification and regression tasks [25][26][27]. DL algorithms are expected to overcome the challenges posed by large-scale data [28]. Moreover, they can learn and discriminate features in a hierarchical way [19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they can learn and discriminate features in a hierarchical way [19]. DL approaches have been applied to various domains of renewable energy and have provided higher forecast accuracy for wind and other renewable energies than traditional methods [19,28]. Recent studies have demonstrated the use of DL techniques and good ML tools for complex pattern detection, regression analysis, and forecasting [29].…”
Section: Introductionmentioning
confidence: 99%